BMJ Learning: Benign prostatic hyperplasia: treatment in primary care. Issue 7567 (7th September 2006) - Patel, Anand K; Chapple, Christopher R
Abstract : This article provides information on how to treat patients with lower urinary tract symptoms that are suggestive of bladder outflow obstruction, secondary to benign prostatic hyperplasia